Spook house volume 2 ebook - Powell, Eric (Spook House, 2023)
A spooky, funny, and sometimes gross, book for kids of all ages!This Albatross Funnybooks anthology features works by some of the greats in the field of horror and humor comics! Such as William Stout, Eric Powell, Steve Mannion, Jake Smith, Kyle Hotz, Dave Johnson, Brett Parson, Robb Mommaerts, Lance Inkwell, Gideon Kendall, and Logan Faerber!